2020
DOI: 10.30773/pi.2019.0305
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Volumetric Correlates of Childhood Trauma, Anxiety, and Impulsivity in Bipolar Disorder

Abstract: Objective More recently, attention has turned to the linkage between childhood trauma and emotional dysregulation, but the evidence in bipolar disorder (BD) is limited. To determine neurobiological relationships between childhood trauma, current anxiety, and impulsivity, we investigated cortical volumetric correlates of these clinical factors in BD.Methods We studied 36 patients with DSM-5 BD and 29 healthy controls. Childhood trauma, coexisting anxiety, and impulsivity were evaluated with the Korean version-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Specifically, BD patients with CAs were compared with other patients without a history of CAs (Janiri et al ., 2017) or with HC (Janiri et al ., 2019) or divided into two groups according to specific genetic vulnerabilities (Aas et al ., 2013, 2014). Other structural studies investigating the possible GM correlates of CAs in BD patients showed volume reductions in the thalamus (Duarte et al ., 2016; Poletti et al ., 2016), alterations in the amygdala (Souza-Queiroz et al ., 2016; Janiri et al ., 2017) and in several frontal regions including the pre-frontal, orbito-frontal, para-central cortices and the middle-frontal gyrus (Duarte et al ., 2016; Poletti et al ., 2016; Song et al ., 2020; Begemann et al ., 2021). As shown in Table 1, these alterations seem to indicate that BD patients with a history of CAs are characterised by volume reductions in all these regions when compared with HC or similar group without a history of CAs.…”
mentioning
confidence: 99%
“…Specifically, BD patients with CAs were compared with other patients without a history of CAs (Janiri et al ., 2017) or with HC (Janiri et al ., 2019) or divided into two groups according to specific genetic vulnerabilities (Aas et al ., 2013, 2014). Other structural studies investigating the possible GM correlates of CAs in BD patients showed volume reductions in the thalamus (Duarte et al ., 2016; Poletti et al ., 2016), alterations in the amygdala (Souza-Queiroz et al ., 2016; Janiri et al ., 2017) and in several frontal regions including the pre-frontal, orbito-frontal, para-central cortices and the middle-frontal gyrus (Duarte et al ., 2016; Poletti et al ., 2016; Song et al ., 2020; Begemann et al ., 2021). As shown in Table 1, these alterations seem to indicate that BD patients with a history of CAs are characterised by volume reductions in all these regions when compared with HC or similar group without a history of CAs.…”
mentioning
confidence: 99%
“…Indeed, recent studies on the impact of anxiety symptoms in bipolar disorder demonstrated unfavorable outcomes or a worse prognosis (Lorenzo-Luaces et al, 2018;Spoorthy et al, 2019;Kim et al, 2021). For instance, a significant association between anxiety symptoms and gray matter volume deficits in the left middle frontal lobe was presented, which implies neural evidence of the anxiety symptoms in BD (Song et al, 2020). Furthermore, there were predictors whose associations with cognitive domains are minimal, such as age of onset, depression severity, past mood disorder history, and impulsiveness.…”
Section: Discussionmentioning
confidence: 95%
“…When controlling for TIV, significant relationships appear that were not previously significant and those that were already present when TIV was not taken into account are maintained. Previous studies have also found differences in the statistical power of the relationships between personality traits and GMV depending on the control variables used [ 74 , 77 , 78 ]. The point that when not controlling for TIV our results show a reduction in the number of structures that are related to personality traits may be due to the fact that these relationships appear but cannot be observed because they are masked by a TIV that is not being taken into account.…”
Section: Discussionmentioning
confidence: 99%